Challenging the Philosophical Axis Enactment in the Sustainability of Malioboro Street Vendors’ Relocation - Kardanardi, Lucky; Syahdani, Muwalliha (IKAT: The Indonesian Journal of Southeast Asian Studies, 2023)
In enacting its "Philosophical Axis", the Government of Yogyakarta forged a significant policy thattransformed its relations with community members especially street vendors. Under this policy,street vendors were relocated from their previous locations to sites known as Teras 1 and Teras 2Malioboro. Although the Operational Guidelines for the Implementation of the World HeritageConvention mandate the practice of sustainable development, street vendors—the economicbackbone of the Special Region of Yogyakarta—indicate that they have experienced a drastic loss ofincome due to accessibility issues. This research explores the impact of relocation on street vendors'income as well as short, medium, and long term plans for the new sites. Data were collected throughquestionnaires that were distributed to ninety respondents from Teras 1 and Teras 2, in-depthinterviews, and a review of the literature.